О гибридном словосложении в русском языке в эпоху глобализации - Elena Koriakowcewa (Studia Rossica Posnaniensia)
The article describes in detail some derivational elements involved in the process of agglutination occurring in word-formation system of modern Russian, analyzing semantic and functional characteristics of these word-building elements. The comprehensive analysis of the collected hybrid derivatives shows that globalization and the Anglo-American ‘linguistic hegemony’ increased the productivity of international morphemes, penetrating into the Russian word-formation system through the mass media. Modern Russian language has been undergoing noticeable changes in word-formation models and in the inventory of actively productive derivational affixes. The following processes are noticeable: 1) resemantization and activation of international affixes; 2) development of new hybrid derivative models; 3) creation with the help of morphemes abstracted from composites new formally and semantically condensed nouns, which allows to notice an agglutination’s tendency.